The prognostic significance of CD63 expressionin patients with non-small cell lung cancer - Hyun Koh; Hyo An; Jae Jung; Dae Song (Polish Journal of Pathology, 2019)
CD63 has been suggested to participate in tumorigenesis, invasion, and metastasis. In this study, we aimed to investigate the prognostic significance of CD63 expression in non-small cell lung cancer (NSCLC). CD63 expression was evaluated in 133 cases of NSCLC via immunohistochemical staining using tissue microarray blocks. We assessed the relationship between CD63 expression and clinicopathological characteristics, as well as the prognostic significance of CD63 expression in NSCLC. CD63 expression was significantly correlated with patient gender (p < 0.001), smoking history (p = 0.020), histologic type (p < 0.001), tumour stage (p = 0.016), lymph node metastasis (p = 0.034), and TNM stage (p = 0.007). A multivariate Cox proportional hazards regression analysis determined low CD63 expression to be an independent factor for unfavourable disease-free survival (DFS) (HR = 2.043, 95% CI: 1.035-4.035, p = 0.040), and Kaplan-Meier analysis indicated that the low CD63 expression group showed significantly lower DFS than the high CD63 expression group of patients with NSCLC (p = 0.019). Low CD63 expression might be an unfavourable prognostic factor in patients with NSCLC.